Complications of instrumental vaginal deliveries and associated factors in hospitals of Western Oromia, Ethiopia. (July 2022) - Shimalis, Chaltu; Hasen, Tahir; Regasa, Misganu Teshoma; Desalegn, Zelalem; Mulisa, Diriba; Upashe, Shivaleela P
Objective: In developing countries like Ethiopia, there is lack of evidence that shows the magnitude and factors affecting complications of instrumental delivery. Most of the research done in Ethiopia was secondary data and lacks variables like socio-demographic factors, availability of cardiotocograph, number of traction, and who conducted delivery (qualification of health workers). So, this study tried to fill the gaps by conducting primary research with secondary data and adding those variables stated above. Methods: Health facility-based cross-sectional study was conducted from 20 February 20 June 2020 in five public hospitals in East Wollega Zone. Single population proportion formula used to calculate sample size. Systematic random sampling was employed. Interviewer-administered structured questionnaire, checklist, and document review were used to collect data from 282 respondents. Data entered to Epi Data version 3.01 and exported to a statistical package of social sciences version 21 for analysis. Those variables with p < 0.25 in the bivariate analyses were a candidate for multivariable logistic regression and multivariable logistic regression was done to identify factors associated with complications of instrumental vaginal delivery using 95% confidence interval and p < 0.05. Results: Complications of instrumental vaginal delivery were 37.2%. Out of all neonates delivered by operative vaginal delivery, 69 (24.5%) developed complications. Vacuum-assisted delivery (adjusted odd ratio = 0.245, 95% confidence interval 0.092–0.658), 120–160 fetal heartbeats per minute (adjusted odd ratio = 0.298, 95% confidence interval 0.114–0.628), birthweight > 4000 g (adjusted odd ratio = 4.09, 95% confidence interval 1.729–9.499) and outlet instrumentation (adjusted odd ratio = 0.139, 95% confidence interval 0.057–0.339) were associated with complications of instrumental vaginal delivery. Conclusion: Magnitude of complications of instrumental vaginal delivery was high in the study area. So, health professionals should give due attention on instrument selection and application. Instrumental delivery requires a careful assessment of clinical circumstances to identify the indications and contraindications for the application of the instruments.